Aeration effects on water-structure impacts:Part 2. Wave impacts on a truncated vertical wall - Mai, T. (2020)
Aeration effects on wave loading are of considerable importance for offshore design. This paper describes experimental work to investigate four types of wave impact on a truncated vertical wall (representative of a plate in an FPSO vessel), in pure and aerated water. Investigations showed that high aeration and flip-through wave impacts are the most severe impact types and should therefore be considered for offshore structure design. It was also observed that there is a significant reduction in peak impact loads (both pressure and force) for impacts in aerated water compared to those in pure water. However, there was almost no reduction in impulsive loadings in aerated water compared to those in pure water, and therefore maximum instantaneous loads may be conservative in the presence of aerated water, in the implementation for offshore structure design. This paper is a companion paper to “Aeration effects on water-structure impacts: Part 1. Drop plate impacts”.